Modelling an asphalt pavement in Portugal - Ionescu, Andrei Gabriel (2007)
This article presents the modelling procedure of an existent pavement in Portugal, carried out by the author in the frame of “Leonardo da Vinci” Student Mobility Program, Contract RO/2004/PL93209/S, at Universidade do Minho - Center of Civil Engineering. The 6 years old pavement under study exhibited an important extent of cracking and ravelling with high severity level, indicative of premature failure. The assessment of the structural condition of the pavement requires the definition of its model. The adopted model is based on multilayer elastic (MLE) theory as it is one of most used models. The establishment of the model comprised several tasks, such as: i) surface condition assessment, based on visual inspection; ii) coring in and out of the wheel path and over cracks; iii) deflection measurement by means of a falling weight deflectometer; iv) definition of homogeneous subsections; v) back calculation of the stiffness moduli using Bisar 3.0 Program; vi) temperature correction. The back calculation of the stiffness modulus presented some difficulties as far as curve fitting is concerned. This might have been a consequence of using simplified models. Therefore, further research should focus this topic.